Get the most out of your questions with the extensive resources available on IDNLearn.com. Our Q&A platform offers detailed and trustworthy answers to ensure you have the information you need.
Sagot :
To determine if there is an extraneous solution to the equation [tex]\(\sqrt{x-3} = x - 5\)[/tex], let's carefully solve the equation step-by-step and check for any extraneous solutions.
1. Isolate the square root:
The given equation is [tex]\(\sqrt{x-3} = x - 5\)[/tex].
2. Square both sides:
To eliminate the square root, we square both sides of the equation:
[tex]\[ (\sqrt{x-3})^2 = (x - 5)^2 \][/tex]
Simplifying each side:
[tex]\[ x - 3 = (x - 5)^2 \][/tex]
3. Expand the squared term:
Expanding the right side of the equation:
[tex]\[ x - 3 = x^2 - 10x + 25 \][/tex]
4. Rearrange to form a quadratic equation:
Bring all terms to one side to set the equation to zero:
[tex]\[ 0 = x^2 - 10x + 25 - (x - 3) \][/tex]
Simplify:
[tex]\[ 0 = x^2 - 11x + 28 \][/tex]
5. Solve the quadratic equation:
To solve [tex]\(x^2 - 11x + 28 = 0\)[/tex], we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -11\)[/tex], and [tex]\(c = 28\)[/tex].
The discriminant is:
[tex]\[ \Delta = (-11)^2 - 4 \cdot 1 \cdot 28 = 121 - 112 = 9 \][/tex]
Thus, the solutions are:
[tex]\[ x = \frac{11 \pm \sqrt{9}}{2} = \frac{11 \pm 3}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{11 + 3}{2} = 7 \quad \text{and} \quad x = \frac{11 - 3}{2} = 4 \][/tex]
6. Check for extraneous solutions:
An extraneous solution is a solution that does not satisfy the original equation [tex]\(\sqrt{x-3} = x - 5\)[/tex] when substituted back.
- For [tex]\(x = 7\)[/tex]:
[tex]\[ \sqrt{7-3} = \sqrt{4} = 2 \quad \text{and} \quad 7 - 5 = 2 \][/tex]
Since both sides are equal, [tex]\(x = 7\)[/tex] is a valid solution.
- For [tex]\(x = 4\)[/tex]:
[tex]\[ \sqrt{4-3} = \sqrt{1} = 1 \quad \text{and} \quad 4 - 5 = -1 \][/tex]
Since both sides are not equal, [tex]\(x = 4\)[/tex] is an extraneous solution.
Thus, there is one valid solution [tex]\(x = 7\)[/tex]. The statement "Yes, the extraneous solution is [tex]\(x = 7\)[/tex]" is incorrect because [tex]\(x = 7\)[/tex] is actually a valid solution. The correct statement is:
- "Yes, the extraneous solution is [tex]\(x = 4\)[/tex]."
1. Isolate the square root:
The given equation is [tex]\(\sqrt{x-3} = x - 5\)[/tex].
2. Square both sides:
To eliminate the square root, we square both sides of the equation:
[tex]\[ (\sqrt{x-3})^2 = (x - 5)^2 \][/tex]
Simplifying each side:
[tex]\[ x - 3 = (x - 5)^2 \][/tex]
3. Expand the squared term:
Expanding the right side of the equation:
[tex]\[ x - 3 = x^2 - 10x + 25 \][/tex]
4. Rearrange to form a quadratic equation:
Bring all terms to one side to set the equation to zero:
[tex]\[ 0 = x^2 - 10x + 25 - (x - 3) \][/tex]
Simplify:
[tex]\[ 0 = x^2 - 11x + 28 \][/tex]
5. Solve the quadratic equation:
To solve [tex]\(x^2 - 11x + 28 = 0\)[/tex], we can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -11\)[/tex], and [tex]\(c = 28\)[/tex].
The discriminant is:
[tex]\[ \Delta = (-11)^2 - 4 \cdot 1 \cdot 28 = 121 - 112 = 9 \][/tex]
Thus, the solutions are:
[tex]\[ x = \frac{11 \pm \sqrt{9}}{2} = \frac{11 \pm 3}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{11 + 3}{2} = 7 \quad \text{and} \quad x = \frac{11 - 3}{2} = 4 \][/tex]
6. Check for extraneous solutions:
An extraneous solution is a solution that does not satisfy the original equation [tex]\(\sqrt{x-3} = x - 5\)[/tex] when substituted back.
- For [tex]\(x = 7\)[/tex]:
[tex]\[ \sqrt{7-3} = \sqrt{4} = 2 \quad \text{and} \quad 7 - 5 = 2 \][/tex]
Since both sides are equal, [tex]\(x = 7\)[/tex] is a valid solution.
- For [tex]\(x = 4\)[/tex]:
[tex]\[ \sqrt{4-3} = \sqrt{1} = 1 \quad \text{and} \quad 4 - 5 = -1 \][/tex]
Since both sides are not equal, [tex]\(x = 4\)[/tex] is an extraneous solution.
Thus, there is one valid solution [tex]\(x = 7\)[/tex]. The statement "Yes, the extraneous solution is [tex]\(x = 7\)[/tex]" is incorrect because [tex]\(x = 7\)[/tex] is actually a valid solution. The correct statement is:
- "Yes, the extraneous solution is [tex]\(x = 4\)[/tex]."
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Your questions find clarity at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.